Attitude and Interest Junior High School Students: How Difference and Correlation in Science Learning - Haryanto Haryanto; Dwi Agus Kurniawan; Neng Early Oktavia; Dea Ristria Ariani; Adriyan Ardi Rahman; Miftahul Zannah Azzahra (Postgraduate, University of Mataram, 2022)
The purpose of this study was to compare the attitudes and interests of students at SMPN 34 Batanghari and MTsN 5 Batanghari. To find out the relationship between the attitudes and interests of junior high school students towards science subjects on environmental pollution. To find out the relationship between the attitudes and interests of MTs students towards science subjects on environmental pollution. The method used in this research is a quantitative method with a comparative type. The results of the description test can be concluded that SMPN 34 Batanghari is superior to MTsN 5 Batanghari. Based on the results of the T test, it can be concluded that there is a comparison between students' attitudes and interests towards environmental pollution material. From the results of the correlation test, there is a relationship between the attitudes and interests of the students of SMPN 34 Batanghari and there is a relationship between the attitudes and interests of the students of MTsN 5 Batanghari